Environmental Problems of Central Asia and their Economic, Social and Security Impacts - Qi, Jiaguo; Evered, Kyle T.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Over the last 60 years, we have recognized increasingly that our world is connected, and the impacts of environmental catastrophes and economic crises in one region of our world have far-reaching and long-lasting consequences globally. Central Asia is a developing region with great potential, but there are valid concerns that current resource management practices are not sustainable, particularly with regard to the management of water resources. Recent changes in social structures, accompanied by regional climate change, have caused substantial environmental changes leading to security concerns in the region. As a result, the local economy has been significantly impacted to the extent that the potential for social unrest is of great concern. This book explores new technologies and adaptation strategies to mitigate these environmental problems and cope with continued environmental change with the ultimate goal of promoting sustainable growth and improved quality of life in the region.
Regional Issues And Assessment Tools -- An Overview Of Environmental Issues In Central Asia -- Modern Problems In Using, Protecting, And Managing Water And Land Resources Of The Aral Sea Basin -- Using Satellite Remote Sensing To Study And Monitor The Aral Sea And Adjacent Zone -- Monitoring Arid Land Surfaces With Earth Observation Techniques: Examples Of Intense And Extensive Land Uses -- Biodiversity Of The Aral Sea And Its Importance To The Possible Ways Of Rehabilitating And Conserving Its Remnant Water Bodies -- Water Scarcity In The Aral Sea Drainage Basin: Contributions Of Agricultural Irrigation Anda Changing Climate -- Use Of Biosensors To Detect And Monitor Chemicals Commonly Used In Agriculture And Terrorist Weapons With The Goal Of Preventing Dangerous Environmental Consequences -- Monitoring Rangeland Ecosystems With Remote Sensing: An Example From Kazakhstan -- Regional Climate, Consequences And Adaptations -- Possible Changes In Agriculture Under The Influence Of Climate Change In Kazakhstan -- Constructing Model-Based Climate Change Scenarios For Southeastern Kazakhstan And The Possibilities For Impact Assessment -- Climate Change And Possible Changes In The Water Regime Of Crops In Northern Kazakhstan -- Estimating Agricultural Adaptation To Climate Change Through Cloud Activation For Northern Kazakhstan -- Dynamics And Structure Of Total Ozone Content Over The Republic Of Kazakhstan In Conditions Of Global Warming -- The Challenge Of Water Provision For Pasture Lands: A Restrictive Factor For Livestock Breeding Development In Kazakhstan -- Ecology And Modern Socio-Economic Conditions In Kazakhstan -- Water Resources And Effective Uses -- Introducing Water Pricing Among Agricultural Producers In Khorezm, Uzbekistan: An Economic Analysis -- Water Scarcity Impacts On Northern Cyprus And Alternative Mitigation Strategies -- Economic Evaluation Of Farmers' Alternatives During Irrigation Water Deficit -- An Evaluation Of Irrigation Water Re-Use In Water Drainage And Collection Networks In Karakalpakstan, Uzbekistan -- The Role Of The Amu Darya Dams And Reservoirs In Future Water Supply In The Amu Darya Basin -- Political Economy And Governance -- Poppy Ecologies And Security In Eurasia: Lessons From Turkey's Past And Present -- Distributive Constraints On Environmental Policy In Central Asia -- Governing Of Environmental Problems And Impacts In Bulgarian Agriculture $1 (BLessons For Central Asian Countries -- Irrigation Of The Amu Darya Banks And Its Role As A Potential Solution For The Poppy Problem -- Using A Value Chain Approach For Economic And Environmental Impact Assessment Of Cotton Production In Uzbekistan -- Strategic Environmental Assessment In The Republic Of Belarus: Status, Problems And Perspectives -- Monitoring Urban Greenery For Sustainable Urban Management.s
Keywords: Environment; Climate change; Environmental management; Ecotoxicology; Pollution; Water pollution; Development economics; Environment; Pollution, general; Environmental Management; Climate Change; Development Economics; Ecotoxicology; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Electronic books